Pengaruh Citra Merek, Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Merek Le Minerale 600ml di Kota Semarang) - Kristina Anindita Hayuningtias; Neijun Eltonia (Jurnal Mirai Management, 2022)
The purpose of the study was to determine the effect of brand image, price perception, and product quality on purchasing decisions of 600ml Le Minerale Bottled Drinking Water in Semarang City. This study uses purposive sampling method for a sample of 150 respondents. The data collection technique used survey methods and the research instrument used a questionnaire with a Likert scale 5. The analysis technique used multiple linear regression. The results showed that brand image and product quality had an effect on purchasing decisions, while price perceptions had no positive effect on purchasing decisions. Keywords: Brand Image, Price Perception, Product Quality, and Purchase Decision